Efektivitas Penggunaan Lembar Kerja Siswa pada Pembelajaran Pendidikan Agama Islam terhadap Hasil Belajar Siswa Kelas V SDN 27 Olo Ladang - Rizal, Andhini Desayra; Muliati, Indah (Lembaga Yasin AlSys, 2023)
The purpose of this study was to describe the effectiveness of using student worksheets in learning Islamic religious education on the learning outcomes of fifth grade students at SDN 27 Olo Ladang. This type of research is quantitative research with one group pretest pre-experimental and posttest design methods. The sample of this research was the fifth grade students of SDN 27 Olo Ladang, which consisted of 20 students consisting of 10 boys and 10 girls. The data in this study were the scores of class V test results at SDN 27 Olo Ladang, which totaled 20 questions in the form of multiple choices on the subject, let's live simply and sincerely. The test questions were carried out twice, namely before using the student worksheets and after using the student worksheets. The research instrument is the test method. Based on the results of the study it can be concluded that the use of student worksheets is effectively used in learning Islamic religious education on the learning outcomes of fifth grade students at SDN 27 Olo Ladang. This is evidenced by the results of student test scores before using student worksheets lower than the test scores after using student worksheets and also proven by the t-test sig.(2-Tailed) value of 0.000 <0.05 which means Ho is rejected and Haha accepted. So it can be concluded that the use of student worksheets is effectively used in learning Islamic religious education on the learning outcomes of fifth grade students at SDN 27 Olo Ladang.